Heretosis of rice hybrids under wetland and dryland conditions - Yap, T. C.; Chang, S. C. (1976)
Many plant breeders have recently become interested in the possibility of exploiting heterosis in self-pollinated cereal crops. The amount of heterosis in wheat (Brown et at. 1966; Knott 1965), barley (Suneson 1962; Yap and Harvey 1971) and rice (Jennings 1966; Saini et at. 1974) has been reported by many workers. The means for producing large quantities of hybrid seeds in these crops has been proposed by several workers (Wiebe 1960;. Harnage 1965; Shinjyo 1969; Wilson 1972).